2019
DOI: 10.1007/s13691-018-00357-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute arteritis after G-CSF administration

Abstract: Granulocyte colony-stimulating factor (G-CSF) is commonly used in clinical practice to accelerate neutropenia recovery after chemotherapy. G-CSF is a myeloid growth factor produced by monocytes, macrophages, fibroblasts and endothelial cells. Generally, aortitis and arteritis are not a known side effect of G-CSF and is thought to be extremely rare. Here, we present a case of a 77-year-old woman who underwent adjuvant chemotherapy (combined paclitaxel and carboplatin) for ovarian cancer, and then developed acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Few case reports showed the aortitis caused by gemcitabine or bevacizumab 30 32 . Similary with the preivous data 8 , 11 13 , 17 19 , docetaxel was concorrently used in our aortitis patients. However, aortitis did not recur during the remainder of docetaxel chemotherapy without G-CSF after aortitis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Few case reports showed the aortitis caused by gemcitabine or bevacizumab 30 32 . Similary with the preivous data 8 , 11 13 , 17 19 , docetaxel was concorrently used in our aortitis patients. However, aortitis did not recur during the remainder of docetaxel chemotherapy without G-CSF after aortitis.…”
Section: Discussionsupporting
confidence: 83%
“…Based on this immune-related vascular inflammation as one of the main mechanisms underlying the development of aortitis, all our patients were treated with short-term steroids to induce immunosuppression. While some data showed spontaneous improvement of aortitis without anti-inflammatory agents 8 , 11 , we thought that the recovery without anti-inflammatory agents might take longer than for the use of glucocorticoid, and delay recovery could directly affect the anticancer treatment schedule. Anticipating no further delay in chemotherapy, it may be reasonable to consider short-term glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 89%
“…A review of 10 published case reports identified from PubMed are summarised in table 1 7–16. The existing case reports describe similar presenting features with patients developing an acute onset of symptoms mimicking an infective picture and most cases describing a rapid resolution of symptoms 7 8 11 12 14–16.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted G-cSF not only has an antiapoptotic effect but also promotes the formation of tumors by mobilizing MdScs to inhibit T cell activity and Bv8 secretion (12). in some clinical case reports, the use of safe therapeutic doses of G-cSF may cause unpredictable side effects such as bone pain, local skin reactions at the injection site and even spleen rupture or infarction (93)(94)(95)(96). This evidence also raised concerns for clinical work.…”
Section: Discussionmentioning
confidence: 99%